Accurate quantification of inter-domain partition coefficients in GUVs exhibiting lipid phase coexistence. Issue 71 (13th July 2016) - Sarmento, M. J.; Pinto, S. N.; Coutinho, A.; Prieto, M.; Fernandes, F.
Abstract : Giant unilamellar vesicles (GUVs) with phase coexistence allow for the recovery of inter-domain partition coefficients ( K p ) of fluorescent molecules through comparison of fluorescence intensities in each phase. Abstract : Giant unilamellar vesicles (GUVs) with phase coexistence allow for the recovery of inter-domain partition coefficients ( K p ) of fluorescent molecules through comparison of fluorescence intensities in each phase. This method has been extensively used to gather qualitative information regarding the preference of both lipid analogues and other fluorescent molecules for insertion into ordered lipid membrane phases, which is often used as a predictor for incorporation in ordered plasma membrane domains. Methods aiming to recover quantitative information on partition properties from GUV imaging fail to correct for brightness and area per lipid differences, skewing recovered values. Additionally, photoselection effects occurring in the presence of linearly polarized excitation are generally neglected in these calculations. Here, we describe a new methodology for correction of fluorescence imaging data obtained from GUVs to recover accurate partition coefficients, which accounts for changes in the probe's quantum yield, area per lipid differences and photoselection effects. This general methodology is used to quantify liquid ordered/liquid disordered lipid phase partition coefficients of several commonly used fluorescent analogues of phospholipids. Importantly, several sources of error in spectroscopic measurements of K p, such as incorporation of a fluorescent probe in domain boundaries, clustering in water or in the membrane, or formation of three coexisting phases, are either irrelevant for quantification of inter-domain K p 's through the method presented here or are readily recognized through imaging with GUVs.